Histological Harmony: A Distinct Case of Mixed Breast Carcinoma in an Elderly Female - Navakodi, Manjula; Anbazhagan, Yogesh (Asian Pacific Journal of Cancer Care, 2025)
Background: Breast cancer is classified morphologically into “Invasive Breast Carcinoma of No Special Type” (IBC-NST) and various special subtypes. Mixed breast carcinoma, characterized by the presence of two or more distinct histological types, poses unique diagnostic challenges and is relatively rare. Case Presentation: A 74-year-old female presented with a six-month history of a lump in her left breast, with no significant family history. Clinical examination revealed an ill-defined lump, and imaging studies indicated a BIRADS score of IV-B. Fine Needle Aspiration Cytology (FNAC) suggested proliferative breast disease with atypia. Surgical excision uncovered two tumors: Tumor 1, an invasive papillary carcinoma, and Tumor 2, exhibiting features of IBC-NST and ductal carcinoma in situ (DCIS). A subsequent Left Modified Radical Mastectomy (MRM) confirmed no residual disease in the specimen or lymph nodes. Immunohistochemistry Results: Both tumors tested positive for estrogen and progesterone receptors and negative for HER2-neu. Tumor 2 displayed a Ki67 index of 8%, indicating low proliferation. Conclusion: This case exemplifies the complexity of mixed breast carcinoma involving IBC-NST and invasive papillary carcinoma. It underscores the importance of histopathological and immunohistochemical analysis in accurately diagnosing and managing such cases. As mixed breast cancers constitute a small percentage of diagnoses, ongoing vigilance and collaboration among oncologists and pathologists are essential for tailored treatment approaches.